H-70: HIGH YIELD MAIZE HYBRID FOR RAINFED AND IRRIGATED OF THE CENTRAL HIGHLANDS OF MEXICO - Arellano Vázquez José Luis; Virgen Vargas, Juan; Rojas Martínez Israel; Avila Perches, Miguel Angel (Revista Mexicana de Ciencias Agrícolas, 2018)
The genetic improvement of maize in Valles Altos, has allowed the development of hybrids with high yield, low bearing and resistance to lodging disease in the past decade; which have been products of the parent lines combination of VallesAltosof INIFAPandCIMMYT(Arellanoetal.,1997). H-70 resulted from that combination as a trilinear hybrid, with white grains and semi-crystalline texture, with favorable adaptation to elevations of 2 200 to 2 600 m, intermediate maturity, as it achieves male flowering or tasseling at 100 days and female or silking at 102 days, on average. Presents plant height of 2.4 m and cob height of 1.4 m. It is resistant to lodging disease and plant and cob diseases. Yield f luctuates from 4 to 13.3 t ha-1, under a density of 65 000 plants ha-1. The cob has an average length of 16 cm, with 18 rows and 34 grains per row. Cob weight is 180 g and the grain/cob ratio is 86%. The average weight of 100 grains is 43.3 g. Harvesting can be done at 180 days, with a grain moisture content of 25 to 26%, so the cob must undergo a drying process to reduce moisture down to 14%. If the producer does not have a dry storage, he can harvest at 210 days with a grain moisture content of 18% to 19% and continue with the natural cob drying. The yields obtained with H-70 exceeded in 13% the yield of commercial hybrids. The genetic constitution of this hybrid allows it to positively thrive at different rainfall levels and planting in areas with rainfall delay until May 15th. Its plant bearing provides intensive planting with 70 000 plants ha-1 for grain production and it has potential for forage production in irrigated areas and a good rainfall. The main economic impact of H-70 is the difference of 3 and 7 t ha-1 over the yield of native seeds, representing 7 to 14 thousand pesos per hectare. This increase makes profitable the maize production.